Peculiarities of approaches to assessing the interchangeability of antiepileptic drugs - E. O. Zhuravleva (Безопасность и риск фармакотерапии, 2018)
The adequacy of the interchangeability of original and generic drugs is an important economic and social problem in healthcare. In this article we look at the problem of the replacement of antiepileptic drugs. Sometimes when their bioequivalence is proved they still can be not equivalent therapeutically. The results of the therapy for these kinds of drugs can differ. As well as the individual characteristics of the metabolism that can affect the results of the treatment, there are other possible factors - the diet of the patient or the time of day,when patient takes medication. The cases when for the replacement of one drug for another it was necessary to have both biological and therapeutic equivalence are described in this article. The research data of interchangeability of neurotropic drugs in different countries are presented. The article provides a classification of the Medicines and Healthcare products Regulatory Agency (MHRA) to estimate the possibility of replacement of drugs with recommendations to minimize the risk of adverse reactions for use in clinical practice.